Transcrição cooperativa de genes ribossomais em Escherichia coli usando um modelo estocástico e dependente de sequência - Nakajima, Rafael Takahiro [UNESP] (2015)
The process that produces messenger RNAs from DNA sequences is called transcription, and these reactions are catalyzed by the RNA polimerase enzyme. Many different experimental techniques have been applied to investigate this process including biochemical techniques, optical and magnetic tweezers, atomic force microscopy and single molecule florescence. These biochemical process studies showed that many RNAP molecules operate simultaneously on a single DNA strand. The number of different molecules depends on cellular demands, concentration of free RNAPs, promoter strength and the presence of transcription factors. Escherichia coli ribosomal genes are a popular experimental model to investigate the transcription process. These genes are essential to cell physiology, and they are strongly expressed. There are evidences that some cellular mechanisms collaborate to accelerate their transcription. In this work we investigate the RNAP collaborative transcription in E. coli ribosomal genes using a stochastic and sequence dependent model proposed by our group. The chemical reactions were simulated using a model based on the Gillespie algorithm. This methodology is a good compromise between computational cost and biological realism and includes some ingredients that were missing in previous theoretical studies. The model considers back and forward tracking elongation and it identifies pauses by determining the dwell time on specific sites. The model also predicts abortive transcription and transcription acceleration due to collaborative RNAP interaction. The E. coli rrnB ribosomal operon sequence was simulated by varying (i) the number of RNAP (R) on the DNA strand, (ii) the interaction force between two colliding RNAPs (F) and (iii) the concentration of nucleoside triphosphate ([NTP]). Our results are promising for F =15 pN, R = 50 and [NTP] ...